2021
DOI: 10.4081/jphr.2021.2232
|View full text |Cite
|
Sign up to set email alerts
|

The Time Pattern of Selenomethionine Administration in Preventing Free Radicals Due to Exposure to Electric Cigarette Smoke

Abstract: Background: Most people believe that electric cigarettes have no negative effect on health,  which causes them to use it more. However, exposure to the smoke from these cigarettes is bad for the health and causes cell damage. Antioxidants play an important role in preventing cell damage, and they can be obtained through the oral administration of selenomethionine.Design and methods: This study used an experimental method and a post-test control group design. Male Wistar rats, which were exposed to cigarette sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Our study highlights the role of aldehyde metabolism in e-cigarette-induced oxidative stress and importantly identifies that inefficient aldehyde metabolism, as for the ALDH2*2 mice, causes higher levels of oxidative stress relative to wild type ALDH2 mice. Other studies also report e-liquid can generate the reactive aldehyde MDA [ [45] , [46] , [47] ]. In addition, we observed that acetaldehyde as the primary aldehyde in e-cigarette aerosol promotes intracellular Ca 2+ influx, with the ALDH2*2 variant further enhanceing the Ca 2+ influx.…”
Section: Discussionmentioning
confidence: 99%
“…Our study highlights the role of aldehyde metabolism in e-cigarette-induced oxidative stress and importantly identifies that inefficient aldehyde metabolism, as for the ALDH2*2 mice, causes higher levels of oxidative stress relative to wild type ALDH2 mice. Other studies also report e-liquid can generate the reactive aldehyde MDA [ [45] , [46] , [47] ]. In addition, we observed that acetaldehyde as the primary aldehyde in e-cigarette aerosol promotes intracellular Ca 2+ influx, with the ALDH2*2 variant further enhanceing the Ca 2+ influx.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 This vegetable also contains selenium, and is known to potentially increase various enzymatic antioxidants, including superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px). 35…”
Section: Articlementioning
confidence: 99%
“…Products exposed to cigarette smoke can cause a prolonged inflammatory response that damages the epithelium of the airways and lung tissue, reduces lung defense mechanisms, and interferes with tissue repair in the lungs. [11][12][13] As frequent smoking can cause symptoms such as dyspnea, increased sputum production, and coughing, these symptoms can be early detection of pulmonary function disorders, namely COPD. 14 Of the symptoms that commonly occur, cough is one of the risk factors for pulmonary function disorders, namely COPD, especially in chronic cough in smokers.…”
Section: Introductionmentioning
confidence: 99%